Current oral contraceptive use affects explicit and implicit measures of depression in women - Hampson, Elizabeth; Abrahamson, Sara N.; Breddy, Taylor N.; Iqbal, Maisha; Wolff, Elena R. (Frontiers in Psychology, 2024)
Some data suggest that increased depressive symptoms may occur in women using combined oral contraceptives (OCs). However, this idea is controversial and the existing evidence is conflicting. The present study compared negative affect in 53 healthy women (Mage = 19.9 yr) during intervals of active daily OC hormone intake and during the washout week of the contraceptive cycle when no exogenous estrogens or progestins are used. A prospective counterbalanced repeated-measures study design was employed. Depressive affect was evaluated using standard psychometric tests of explicit (self-perceived) and implicit negative affect. Implicit measures are considered less subject to bias related to social expectations, self-awareness, or willingness to disclose. Other than their usual OCs, participants were medication-free and had been using OCs for a median of 12 mo. We found that measures of implicit affect (e.g. Affect Misattribution Procedure, Emotional Stroop Test) displayed a more depressive-like pattern of performance during active hormone intake, particularly among a subgroup of OC users who reported experiencing high levels of depressive affect more generally. In contrast, participants' self-perceptions suggested that they perceived their negative symptoms to be greater during the 'off' phase of the OC cycle, when OC steroids are withdrawn and menses occurs. The present findings reinforce the possibility of depressive mood effects associated with OC usage, and highlight the utility of including implicit measures, but also illustrate the complexity of mood assessment in OC users.